Arists under siege : theatre and dictatorial regimes in Uganda / Rose Mbowa. - Mbowa, Rose
This chapter was extracted from the book titled: Theatre and perform ance in Africa edited by Eckhard Breitinger, 1994.
AR/SIC/1/4/5
English
Shelf no. 3
Keywords: Theatre -- Uganda